Psychological Characteristics of the Manifestation of Civil Position in Early and Late Youth - Kochetova, Y.A.; Emelianova, E.A. (Psihologo-pedagogičeskie issledovaniâ, 2019)
The problem of civil position formation is one of the most important tasks of the state and society. There are not enough references to the studies of the specifics and forms of civic activity in the psychological literature. The aim of this research is to study the psychological aspects of citizenship manifestation in early and late youth. The hypothesis was the assumption that the indicators of the civic activity formation increase during the transition from early adolescence to youth and decrease in the period of late adulthood. The study involved 729 subjects (217 boys and 512 girls). The research method is an ascertaining experiment using the "Models of measurement of citizenship: diagnostics of civic activity" questionnaire. On the basis of the obtained results, we can make the conclusion about the formation of the civil position of schoolchildren and students, their active attitude to social reality. The results of the experiment allow us to state that the highest level of development has the parameter of civic activity "the presence of moral guidelines", which decreases in late youth. The presented study can serve as a basis for further study of the issue of civic activity and its psychological regularity. The obtained results can be useful for further practical development, as well as used in training courses on pedagogical psychology and developmental psychology. Формирование гражданской позиции является одной из значимых задач государства и общества. Психологическая литература содержит недостаточное количество ссылок на проведенные исследования, изучающие специфику, особенности, формы гражданской активности. Цель данного исследования — изучение психологических аспектов проявления гражданской позиции в ранней и поздней юности. Гипотезой выступило положение о том, что показатели сформированности гражданской активности повышаются при переходе от подросткового к юношескому возрасту и снижаются в период поздней взрослости. В исследовании приняли участие 729 испытуемых (217 — юноши и 512 — девушки). Методом исследования является констатирующий эксперимент с использованием опросника «Модели измерения гражданственности: диагностика гражданской активности». На основании полученных результатов делается вывод о сформированности гражданской позиции у школьников и студентов, их активном отношении к социальной действительности. Результаты эксперимента позволяют констатировать, что наиболее высокий уровень развития имеет параметр гражданской активности «наличие нравственных ориентиров», который снижается в поздней юности. Представленное исследование может послужить основой для дальнейшего изучения вопроса о гражданской активности и ее психологических закономерностях. Полученные данные могут быть полезны для дальнейших практических разработок, а также использованы в учебных курсах по педагогической психологии и психологии развития.